Laparoscopy-Assisted Vaginal Versus Abdominal Hysterectomy in Endometrial Cancer. Issue 1 (1st January 2010) - Hahn, Ho-Suap; Kim, Hyun-Ja; Yoon, Seok-Geun; Kim, Woo-Chul; Choi, Hong-Jun; Kim, Hy-Sook; Hong, Sung-Ran; Kwon, Yong-Soon; Lee, In-Ho; Lim, Kyung-Taek; Lee, Ki-Heon; Shim, Jae-Uk; et al.
Abstract : Introduction: The purpose of this study was to compare the efficacy of a laparoscopy-assisted surgical staging with a traditional laparotomy staging for the treatment of endometrial cancer. Methods: We retrospectively analyzed the medical records of 465 patients with endometrial adenocarcinoma treated by surgery between January 1996 and December 2007. Results: There were no significant differences between the laparoscopy and the laparotomy groups in age, body mass index, and histologic type. However, in the laparotomy group, grade and surgical stage were higher, the diseases were more chronic, and more postoperative adjuvant treatments were necessary. One hundred seven (76.4%) of 140 patients in the laparoscopy group and 260 (80.0%) of the 325 patients in the laparotomy group had lymphadenectomy, and the median numbers of pelvic and paraaortic lymph nodes obtained were not statistically different. The laparoscopy group showed shorter postoperative hospital stay and lower blood loss, and the operating time was also shorter than that in the laparotomy group. There was no significant difference in intraoperative or postoperative complications, and the operative technique did not influence survival rates after adjusting several confounding factors. Conclusions: Our data of 12 years with a large number of patients show no differences in complications and impacts on survival between laparoscopy and laparotomy. Laparoscopy has advantages of shorter operating time and other advantages over laparotomy previously reported. Therefore, laparoscopy can be considered a good therapeutic option for endometrial cancer.